Mathematical Modeling Of Household Plastic Waste Distribution Management With Transportation Methods - Lilla Afiffah; Adinda Nur Ameliyah; A’idah Nur Hanifah; Rudianto Artiono (Universitas Airlangga, 2023)
Most of the plastic waste is generated by households. Plastic waste is often a problem because there are many and cannot decompose by itself. To solve the problem of plastic waste, plastic waste management will be carried out by channeling plastic waste to the waste bank. Good and correct management of plastic waste distribution is carried out by applying transportation methods starting from modeling the distribution of plastic waste generated from households and solutions from mathematical modeling that is built. From the transportation calculation, the minimum cost of managing the distribution of plastic waste will be obtained so that an efficient plastic waste distribution management system is formed. This study uses the type of experimental research (experimental research) with a literature study. The data used to construct the model are derived from literature studies and simulation data. The results of this study can be developed into a computer program regarding the management of household plastic waste distribution.